2014
DOI: 10.1111/1462-2920.12439
|View full text |Cite
|
Sign up to set email alerts
|

Improved plant resistance to drought is promoted by the root‐associated microbiome as a water stress‐dependent trait

Abstract: Although drought is an increasing problem in agriculture, the contribution of the root-associated bacterial microbiome to plant adaptation to water stress is poorly studied. We investigated if the culturable bacterial microbiome associated with five grapevine rootstocks and the grapevine cultivar Barbera may enhance plant growth under drought stress. Eight isolates, over 510 strains, were tested in vivo for their capacity to support grapevine growth under water stress. The selected strains exhibited a vast arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
245
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 497 publications
(279 citation statements)
references
References 74 publications
7
245
1
5
Order By: Relevance
“…We recognize that the colonization patterns observed in Arabidopsis may not reflect the one occurring in grapevine, but provide hints of the general process of root colonization. Our fluorescent screens on plant roots confirmed that the assayed bacteria were able to colonise the root systems of the plants as previously observed by Rolli et al (2015). Moreover, bacteria may became endophytic and moving from the interior of the roots to other plant tissues (Compant et al 2010;Compant et al 2011;Lareen et al 2016).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…We recognize that the colonization patterns observed in Arabidopsis may not reflect the one occurring in grapevine, but provide hints of the general process of root colonization. Our fluorescent screens on plant roots confirmed that the assayed bacteria were able to colonise the root systems of the plants as previously observed by Rolli et al (2015). Moreover, bacteria may became endophytic and moving from the interior of the roots to other plant tissues (Compant et al 2010;Compant et al 2011;Lareen et al 2016).…”
Section: Discussionsupporting
confidence: 86%
“…The roots inoculated with the B5-gfp and B7-dsRED strains were gently removed from the soil and analysed under the laser-scanning confocal microscope as described for the experiments with Arabidopsis. Finally, the bacteria in the grapevine rhizosphere was analysed using denaturing gradient gel elecrophoresis (DGGE) as described by Rolli et al (2015). The DGGE bands were excised from the gel using a sterile cutter and eluted in 50 μl of water at 37°C for 5 h. The reamplification of DNA eluted from the DGGE bands was performed using 907R and 357F primers without GC-clamps according to the following protocol: 95°C for 5 min, 30 cycles at 95°C for 1 min, 61°C for 1 min, 72°C for 1 min and a final extension at 72°C for 7 min.…”
Section: Experiments With Arabidopsismentioning
confidence: 99%
See 2 more Smart Citations
“…The plant microbiota can influence multiple plant traits such as biomass accumulation (Sugiyama et al 2013), metabolite production , drought tolerance (Lau and Lennon 2012;Rolli et al 2015), flowering time (Wagner et al 2014;PankeBuisse et al 2015;Dombrowski et al 2017) and disease resistance (Busby et al 2016;Ritpitakphong et al 2016;Mendes et al 2011;Santhanam et al 2015).…”
Section: Introductionmentioning
confidence: 99%